Pembuatan E-Brosur Menggunakan Aplikasi Canva Sebagai Media Promosi Produk Jasa Di Instagram Pada PT Bunga Wisata Malang - Luis Subastian (KAMPUS AKADEMIK PUBLISING, 2026)
PT Bunga Wisata is a business operating in the tourism sector located in Karangploso, Malang. The service offered tour packages. Promotional media used Instagram and WhatsApp. The promotional media carried out on Instagram is considered less than optimal and less consistent because the designs of the products and services offered are not yet attractive. This research aims to provide complete and clear information regarding the service products offered by PT Bunga Wisata by creating an E-Brochure using the Canva application which is uploaded to and Instagram. This research used the Action Research with planning, action, observation and reflection research procedures. Research data was obtained through distributing questionnaires which were distributed to 1 owner, 2 marketing experts, 2 design experts, 10 consumers. design effectiveness was carried out using the EPIC (Empathy, Persuasion, Impact, Communication) method. The highest average score is in the Impact dimension which is in the 'very effective' category. This is because the E-Brochure design is designed to add and provide complete knowledge regarding the products and services offered. The conclusion is that the E- Brochure is designed to be very effective for use as promotional media on PT Bunga Wisata's. The conclusion from this research is that E-Brochures designed using Canva are very effective for use as promotional media on PT Bunga Wisata's Instagram. It is hoped that they can create design updates with the aim of serving as a reminder to consumers or potential consumers